2016
DOI: 10.1371/journal.pone.0147273
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide mRNA Expression Profile in Caenorhabditis elegans under Prolonged Exposure to 1750MHz Radiofrequency Fields

Abstract: ObjectiveC. elegans has been used as a biomonitor for microwave-induced stress. However, the RF (radiofrequency) fields that have been used in previous studies were weak (≤1.8W/kg), and the bio-effects on C. elegans were mostly negative or ambiguous. Therefore, this study used more intense RF fields (SAR = 3W/kg) and longer time course of exposure (60h at 25°C, L1 stage through adult stage) to investigate the biological consequences of 1750 MHz RF fields in wild-type worms.MethodsThe growth rates and lifespans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…At present, the biological effects of microwaves on C. elegans have rarely been studied, and the results have been inconsistent [Bojjawar et al, 2006;Cucurachi et al, 2013;Fasseas et al, 2015;Shi et al, 2015;Gao et al, 2016;Sun et al, 2019]. One study investigated C. elegans exposed to 35 GHz millimeter waves with an average power of 1.52 W for 2-5 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the biological effects of microwaves on C. elegans have rarely been studied, and the results have been inconsistent [Bojjawar et al, 2006;Cucurachi et al, 2013;Fasseas et al, 2015;Shi et al, 2015;Gao et al, 2016;Sun et al, 2019]. One study investigated C. elegans exposed to 35 GHz millimeter waves with an average power of 1.52 W for 2-5 min.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that millimeter waves could cause obvious damage as shown by slow growth and development in C. elegans [Gao et al, 2016]. However, the growth and development were significantly accelerated by microwave exposure at 0.9 and 1.75 GHz, respectively [Gao et al, 2016]. Gao also controlled the temperature consistency of the exposed group and the non-exposed group through the sXc-1800 exposure system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only three in vivo studies evaluated the genome-wide mRNA expression profile using the Illumina sequencing technology, reporting differentially expressed genes in Caernorhabditis elegans after prolonged exposure to 1.75 GHz (SAR = 3 W/kg) [ 62 ] and in some genes related to energy metabolism in budding yeast after exposure to 50 Hz and 2.0 GHz [ 63 ]. A more recent study performed on Escherichia coli K-12 DH5α exposed to 2.4 GHz for 5 h reported that most of the genes identified were involved in many cellular and metabolic processes [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…For C. elegans, which are exposed to non-thermal electromagnetic waves, induced some changes such as conformational damages to cellular proteins, opposite effects on growth and egg production[35]. In an opposite-minded research, after prolonged exposure to 1750 MHz RF fields, no effect was observed on longevity and development of C. elegans[36]. No significant differences were reported by another research group between exposed and sham exposed groups for lifespan, fertility, growth, memory, ROS, apoptosis or gene expression of C. elegans[37].…”
mentioning
confidence: 99%